Simplified video-assisted one-trocar diverting colostomy in pediatric patients - Diego Falchetti; Maristella Pellegrino; Marco Lanata; Salvatore Argento; Lucia Corasaniti; Antonio Dessanti (Elsevier, 2021)
Background: In pediatric age colostomy is mainly temporary and totally diverting, the major indication being neonatal anorectal malformation for which a specific double separated stoma route has been widely popularized. Out of newborn age the reasons for colon diversion in children are less common and the procedures are quite similar to the techniques employed in adults. Laparoscopy for pediatric colostomy has a short history and the original recommended procedure for newborns has been achieved only very recently with a two-trocars technique. Methods: We describe an original one-trocar method to create a double or single totally diverting colostomy avoiding any other abdominal wound at risk for complications. The procedure has been performed on newborns with anorectal malformations as well as on a teenager through minor technical variants. Results: This one-trocar method allowed a quick and safe totally diverting colostomy in every treated patient. There was no complication during surgery and no skin infection in the whole postoperative period; at the end of treatment scars were minimal. Conclusions: This technique is suitable for the specific neonatal double separated colostomy and virtually for every indication of fecal stream diversion in any kind of patient.